World War Two : a military history - Black, Jeremy 1955- (Warfare and history, 2003)
Background -- Initial attacks -- The war widens -- Attacks held, 1942 -- Mounting Allied pressure, 1943 -- Defeating the Axis, 1944 -- The fall of the Axis -- Contexts -- Struggle reviewed